Mineral contents of native bluestem pastures - Harbers, L.H.; Umoh, J.E.; Raiten, D.A.; Chaffin, V.K. (Kansas State University. Agricultural Experiment Station, 2011)
Handclipped and esophageal samples of burned and control native bluestem pastures were taken monthly. Burning increased phosphorus (P) and magnesium (Mg) and decreased iron (Fe). These studies indicate that burned and unburned pastures need to be supplemented with potassium (K), magnesium (Mg), and possibly phosphorus (P) during late fall and winter. A supply of sodium (Na) is necessary continuously.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Bluestem pastures; Phosphorus; Magnesium; Iron